“Corruption mocking at justice” : a theological-ethical perspective on public life in Tanzania and its implications for the Anglican Church in Tanzania - Sebahene, Alfred uw’Imana (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.